Dietary Restraint Partially Mediates the Relationship between Impulsivity and Binge Eating Only in Lean Individuals: The Importance of Accounting for Body Mass in Studies of Restraint - Coffino, Jaime A.; Orloff, Natalia C.; Hormes, Julia M. (Frontiers in Psychology, 2016)
Binge eating is characteristic of eating and weight-related disorders such as binge eating disorder, bulimia nervosa, and obesity. In light of data that suggests impulsivity is associated with overeating specifically in restrained eaters, this study sought to elucidate the exact nature of the associations between these variables, hypothesizing that the relationship between impulsivity and binge eating is mediated by restrained eating. We further hypothesized that the role of dietary restraint as a mediator would be moderated by body mass index (BMI). Study participants (n = 506, 50.6% female) were categorized based on self-reported BMI as under- and normal weight (BMI < 25, 65.8%, n = 333) or overweight and obese (BMI ≥ 25, 34.2%, n = 173) and completed the “restrained eating” subscale of the Dutch Eating Behavior Questionnaire, the “difficulties with impulse control” subscale of the Difficulties with Emotion Regulation Scale, and the Binge Eating Scale. Findings provide initial evidence for the hypothesized moderated mediation model, with dietary restraint partially mediating the relationship between impulsivity and binge eating severity only in lean respondents. In respondents with overweight or obesity, impulsivity was significantly correlated with binge eating severity, but dietary restraint was not. Findings inform our conceptualization of dietary restraint as a possible risk factor for binge eating and highlight the importance of accounting for body mass in research on the impact of dietary restraint on eating behaviors.